Surgical management of odontogenic keratocyst associated with Gorlin-Goltz syndrome.Case report - Vinitzky Brener , Ilan (2024)
Gorlin-Goltz syndrome or basal cell nevi syndrome is an ectodermal neoplasia of autosomal dominant inheritance. It is a multisystem disease with a prevalence of 1 case per 57 000 to 150 000 people. It predominates in patients between the second and third decade of life, with a predilection for the male sex., Iit’s characterized by the presence of multiple basal cell nevus carcinomas, development of odontogenic keratocystic and palmo-plantar pits or dimples and calcification of the falx brain. Odontogenic keratocysts (OKC) occur in more than 80% of cases of patients with Gorlin-Goltz syndrome (GGS). OKC can present as the first sign of GGS. Approximately 65% of cases affect the mandible, with high frequency in the molar and ramus region. A clinical case is presented of a 35-year-old male patient with a current condition of missing teeth. Physical examination revealed syndromic facies. Orthopantomography is requested, observing multiple radiolucent areas of various sizes as well as retained dental organs, so vacuum puncture and incisional biopsy were taken.; Histopathological result: odontogenic keratocyst and suspicion of GGS because the patient meets the major and minor criteria; complementary studies were requested to confirm the diagnosis. Enucleation of cystic lesions with peripheral ostectomy, extraction of retained and excision of the skin lesion was performed under general anesthesia. After one year, the healing process and bone regeneration was observed without signs of recurrence. The patient was kept under control and monitored by our service with annual appointments.